LINGUISTIC COMPETENCE AND SPEAKING PERFORMANCE OF ENGLISH EDUCATION STUDY PROGRAM STUDENTS OF SRIWIJAYA UNIVERSITY - Dwi Wahyuni; Diemroh Ihsan; Rita Hayati (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2014)
Abstract:The objectives of this study were to find out whether or not there was (1) a significant correlation between linguistic competence (LC) and speaking performance (SP), and (2) a contribution of linguistic competence to speaking performance. The method of the study was a correlational study. The population was the fourth, sixth, and the eighth semester students of English Education Study Program, Sriwijaya University in academic year of 2013/2014. The total number of the sample was 100 students. In this study, the students were given two kinds of tests, that is, linguistic competence test and speaking test used to measure the two main variables (LC and SP). The data obtained from the tests were analyzed by using Pearson Product Moment Coefficient on SPSS program for windows. The findings showed that there was a significant correlation between students’ linguistic competence and their speaking performance. The correlation coefficien between linguistic competence and speaking performance was 0.315 and the correlation was low or weak. Furthermore, it was found that the influence of linguistic competence on speaking performance was 9.9 %. It is concluded that linguistic competence gave contribution to students’ speaking performance. Key words:linguistic competence, correlation, speaking performance